Pendampingan Perancangan Sistem Pembukuan Sederhana serta Analisis Kendala Operasional Produksi pada UMKM - Aprilia Riska Rahmawati; Nugraeni Nugraeni (Lembaga Pengembangan Kinerja Dosen, 2026)
The community's economy is supported by the presence of Micro, Small, and Medium Enterprises (MSMEs) however, many MSME owners still face challenges in managing their financial and operational activitie. This community assistance program was conducted at a tailoring MSME in the Special Region of Yogyakarta that experienced two main problems: the absence of a simple bookkeeping system and frequent sewing machine breakdowns that disrupted production activities. The purpose of this program was to assist the business owner in implementing a simple bookkeeping system and improving understanding of machine maintenance to support operational efficiency. Observation, interviews, and direct assistance to the business owner were conducted as the methods employed in this activity. The results showed that before the assistance program, business transactions were not recorded systematically, and personal finances were mixed with business finances. In addition, sewing machine maintenance was only carried out when damage occurred. Through the assistance program, the business owner gained a better understanding of transaction documentation, simple bookkeeping practices, the separation of personal and business finances, and the importance of routine machine maintenance. This program is expected to improve financial and operational management, thereby supporting business sustainability and long-term growth.